“MENINGKATKAN SISTEM PEMBINAAN WARGA BINAAN PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN (LAPAS) SEBAGAI UPAYA UNTUK MEMAKSIMALKAN PENEGAKAN HUKUM“ - Rohmad Taufiq (Program Studi Hukum Keluarga Islam, 2018)
In the criminal justice system in Indonesia, correctional institutionsare one of the pillars in implementing law enforcement.in essencethe prisoners are as human beings and human resources who mustbe treated well and humanely in an integrated coaching system. Inthe correctional system there are two missions and goals to beachieved. First, as a punishment (punishmen), namely an effort toimplement enforcement, legal certainty and to cause a deterrenteffect second, as an improvement (treatment) which is an effortdirected to education, coaching, training and prevention which alllead to the goal of improving the preparation and enlightening ofthe future of prisoners. The treatment of prisoners is based onPancasila and the 1945 constitution, which is the final part of thecriminal system.in this case the penitentiary system is a series oflaw enforcement that aims to make prisoners aware of theirmistakes, improve themselves and not repeat the crime, so that theycan be accepted again by the community, can actively play a rolein development and can live fairly as good, righteous citizens andresponsible.